Revision of Meiodorvillea Jumars, 1974 (Annelida: Dorvilleidae) including descriptions of three new species from the Southwestern Atlantic Ocean. - Rafael de Oliveira Bonaldo; Tatiana Menchini Steiner; Antônia Cecília Zacagnini Amaral (PLoS ONE)
Meiodorvillea Jumars, 1974 is a little-known genus of Dorvilleidae Chamberlin, 1919, characterized by its small size and reduced appendages and jaw apparatus. A revision of the genus is presented, including analysis of the type material of M. minuta (Hartman, 1965) and M. apalpata Jumars, 1974, as well as specimens collected from shelf and slope continental areas in Brazil. A neotype was designated for M. minuta and its distribution was extended to Brazil. The identity of M. chilensis (Hartmann-Schröder, 1965) is questioned and three new species from 21 to 1,300.7 meters depth are also described. Meiodorvillea penhae sp. nov. has furcate chaeta only in the first anterior chaetigers. In contrast, Meiodorvillea hartmanae sp. nov. has very small palps and asymmetrical thin furcate chaeta and Meiodorvillea jumarsi sp. nov. has dorsal cirri and geniculate chaeta only in the first anterior chaetigers.